Short-process preparation method of strong-hydrophobicity passive film on surface of titanium-zinc plate
Through the treatment of pickling-water washing-passivation-drying-aging, and acoustic-flow coupled cavitation treatment during passivation, the titanium zinc plate passivation film is solved by complex process, energy consumption and insufficient durability of the titanium zinc plate passivation film. The problem of this paper has achieved efficient and environmentally friendly preparation of strong hydrophobic passivation film.
Patent Information
- Application Number
- CN202411653482.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The passivation film process of existing titanium zinc plates is complex and consumes timely energy. The passivation agent components are harmful to the environment and have insufficient durability.
The treatment method of pickling-water washing-passivation-drying-aging is adopted, and the acoustic-flow coupled cavitation is performed during passivation, and an environmentally friendly alkaline passivation agent is used to generate a strongly hydrophobic passivation film.
The passivation film production process is significantly shortened, production efficiency is improved and energy consumption is reduced. The prepared passivation film has strong hydrophobicity and self-cleaning properties, improving corrosion resistance and durability.
Smart Images

Figure CN119465126A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material surface treatment. Background Art
[0002] The corrosion resistance of titanium zinc sheet is mainly attributed to a dense natural passivation protective layer formed on its surface. This passivation film is formed by the reaction of zinc with water, oxygen and carbon dioxide in the environment, usually zinc hydroxide or basic zinc carbonate, which provides additional protection for titanium zinc sheet. However, the process of naturally forming a passivation film is slow and greatly affected by environmental conditions, resulting in uncertainty in the results; at the same time, the color of the natural passivation film does not meet the requirements of architectural aesthetics.
[0003] In order to solve these problems, the industry adopts an accelerated passivation process, through chemical treatment such as pickling or phosphating, to form a uniform and dense artificial passivation film for the titanium zinc plate before leaving the factory. This artificial passivation film not only improves the corrosion resistance of the titanium zinc plate, but also gives the material certain self-healing properties. When the surface of the titanium zinc plate is damaged, the zinc element will react with the water and oxygen in the environment to re-form the passivation film, and the color of the newly formed passivation film will gradually become consistent with the color of the surrounding plates, thereby achieving a self-healing effect. The service life of the titanium zinc plate after passivation can be significantly extended. Depending on the different use environments, its durability can reach 80 to 100 years, and even more than 200 years in some ideal environments. In addition, the self-healing properties of the titanium zinc plate not only help maintain the integrity of its appearance, but also help to extend its service life and reduce maintenance costs.
[0004] In practical applications, the passivation film of titanium zinc sheet also gives the material the opportunity to shine in all walks of life. The passivation film can effectively prevent oxidation, extend the service life of building materials, and reduce maintenance costs; it helps to improve the durability of materials and ensure the performance of automobiles in harsh environments; it improves corrosion resistance and can withstand high and low temperature environments to ensure the safety and reliability of aerospace equipment components; used in housings and other components, the passivation film can effectively prevent electrochemical corrosion and protect internal components from damage. Over time, the passivation film will gradually present a unique color, and this natural aging result will give the titanium zinc sheet a unique sense of history and beauty. Therefore, titanium zinc sheet is not only a high-performance metal material, but also a material with high aesthetic value.
[0005] Up to now, the passivation production process technology of titanium zinc plate is not perfect enough. The preparation of the passivation film of traditional titanium zinc plate needs to go through the steps of pickling-water washing-alkali washing-water washing-passivation-drying-aging. The passivation process not only has economic problems such as energy consumption and time consumption, but also many components of the passivating agent used have environmental impact and toxicity problems. For example, chromic acid passivation has not been widely used in industrial production due to its weak toxicity and possible pollution to the sewage treatment system, as well as high cost. At the same time, the traditional passivation film always has problems with uniformity and density. Furthermore, the increasingly severe global environmental problems have also put forward higher requirements for the corrosion resistance and durability of the passivation film. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of complicated process, energy and time consumption, environmental damage and insufficient durability of the passivation film prepared by the existing method of titanium zinc plate, and to provide a short-process preparation method of a strong hydrophobic passivation film on the surface of titanium zinc plate.
[0007] Although the traditional passivation process can improve the corrosion resistance of titanium zinc plate, the durability of the passivation film is still a problem. In certain extreme environments (such as high humidity, high temperature, acidic or alkaline environment), the traditional passivation film may gradually fail, thereby affecting the corrosion resistance of the titanium zinc plate. This is because the traditional passivation film does not have hydrophobicity, so it is in contact with moisture, oxygen, carbon dioxide, etc. in the air for a long time, and its properties will gradually change, leading to the degradation of the film layer. The passivation film prepared by the present invention has strong hydrophobicity and can avoid contact with water during use, thereby further improving the corrosion resistance and durability.
[0008] A short-process preparation method of a strong hydrophobic passivation film on the surface of a titanium-zinc plate is specifically completed by the following steps:
[0009] 1. Pickling:
[0010] Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for a period of time to obtain a pickled titanium zinc plate;
[0011] 2. Washing:
[0012] The pickled titanium-zinc plate is placed in water for rinsing to obtain a water-washed titanium-zinc plate;
[0013] 3. Passivation:
[0014] ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent;
[0015] ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 10kHz to 100kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0016] 4. Drying:
[0017] The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate;
[0018] 5. Natural aging:
[0019] The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time. After the natural aging, a titanium-zinc plate with a silver-white passivation film having strong hydrophobicity and self-cleaning properties on the surface is obtained.
[0020] Principle of the present invention:
[0021] The present invention proposes a short-process preparation method of a strong hydrophobic passivation film on the surface of a titanium-zinc plate, which adopts a treatment method of pickling-washing-passivation-drying-aging, and develops an alkaline passivator with less environmental harm; during passivation, an acoustic-fluid coupled cavitation treatment is performed to generate strong hydrophobic substances such as orthozinc titanate, thereby achieving the purpose of quickly generating a strong hydrophobic passivation film. Compared with the traditional preparation method of the titanium-zinc plate passivation film, the present invention has the following advantages:
[0022] (1) The passivation film prepared by the present invention has strong hydrophobicity and self-cleaning properties, which can greatly enhance its corrosion resistance in practical applications;
[0023] (2) Greatly shorten the passivation film production process, which can effectively improve production efficiency and reduce energy consumption;
[0024] (3) Acid and alkali solutions with lower concentrations are used as pretreatment agents and passivation agents, which are relatively environmentally friendly;
[0025] (4) The silver-white passivation film prepared by the present invention has excellent corrosion resistance and appearance, which improves its practical value;
[0026] (5) The present invention introduces acoustic-fluid coupled cavitation treatment during passivation, which ① greatly enhances the intensity of the cavitation phenomenon; under the action of sound waves, the cavitation bubbles generated in the liquid will rapidly expand and burst, releasing high-energy shock waves and heat, thereby improving the efficiency of the treatment; compared with simple fluid cavitation, acoustic-fluid coupled cavitation can produce a stronger local high temperature and high pressure environment, causing more bubbles to burst and achieve a stronger physical cleaning effect. ② Acoustic-fluid coupled cavitation can achieve a strong cavitation effect at a lower energy input through the low-frequency excitation of sound waves. This means that under certain conditions, energy consumption can be reduced, and the economy and environmental friendliness of the treatment can be improved. ③ Acoustic-fluid coupled cavitation usually does not produce harmful gases or waste, which makes the process highly environmentally friendly in the field of passivation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The process flow chart of the short-process preparation method of a strong hydrophobic passivation film on the surface of a titanium-zinc plate of the present invention;
[0028] Figure 2 The figure shows the comparison between the common passivation film and the strong hydrophobic passivation film. (a) is the common passivation film prepared by the prior art, and (b) is the silver-white passivation film with strong hydrophobicity and self-cleaning properties prepared in Example 1.
[0029] Figure 3 This is a physical picture of a titanium zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface prepared in Example 1;
[0030] Figure 4 This is a physical picture of a titanium zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface prepared in Example 2;
[0031] Figure 5 This is a physical picture of a titanium zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface prepared in Example 3;
[0032] Figure 6 This is a physical picture of a titanium zinc plate having a silvery white passivation film with strong hydrophobicity and self-cleaning properties on the surface prepared in Example 4;
[0033] Figure 7 This is a physical picture of a titanium zinc plate with a passivation film on the surface prepared in Comparative Example 1;
[0034] Figure 8 This is a physical picture of the titanium zinc plate with a passivation film on the surface prepared in Control Example 1. DETAILED DESCRIPTION
[0035] Specific implementation method 1: This implementation method is a short-process preparation method of a strong hydrophobic passivation film on the surface of a titanium zinc plate, which is specifically completed in the following steps:
[0036] 1. Pickling:
[0037] Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for a period of time to obtain a pickled titanium zinc plate;
[0038] 2. Washing:
[0039] The pickled titanium-zinc plate is placed in water for rinsing to obtain a water-washed titanium-zinc plate;
[0040] 3. Passivation:
[0041] ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent;
[0042] ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 10kHz to 100kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0043] 4. Drying:
[0044] The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate;
[0045] 5. Natural aging:
[0046] The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time. After the natural aging, a titanium-zinc plate with a silver-white passivation film having strong hydrophobicity and self-cleaning properties on the surface is obtained.
[0047] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the volume ratio of sulfuric acid to nitric acid in the pickling solution described in step 1 is 1:1; the total concentration of sulfuric acid and nitric acid in the pickling solution described in step 1 is 15 mL / L to 45 mL / L. The other steps are the same as those in specific implementation method 1.
[0048] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass fraction of sulfuric acid in step 1 is 95% to 98%, and the mass fraction of nitric acid is 63% to 68%. The other steps are the same as those in specific implementation method 1 or 2.
[0049] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the composition of the titanium zinc plate described in step 1 is as follows by mass percentage: Cu: 0.08% to 1.0%, Ti: 0.07% to 0.5%, Al≤0.015%, and the balance is Zn; the thickness of the titanium zinc plate described in step 1 is 0.3mm to 3mm. The other steps are the same as those of specific embodiments 1 to 3.
[0050] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that: the temperature of the pickling solution in step 1 is 25°C to 50°C; the pickling time in step 1 is 1 min to 10 min. The other steps are the same as those in specific implementation methods 1 to 4.
[0051] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that the washing time in step 2 is 1 min to 10 min. The other steps are the same as those in specific implementation methods 1 to 5.
[0052] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the concentration of sodium hydroxide in the alkaline passivating agent described in step 3① is 20g / L~80g / L, the concentration of sodium phosphate is 20g / L~80g / L, the concentration of sodium carbonate is 5g / L~25g / L, and the concentration of sodium silicate is 5g / L~25g / L. The other steps are the same as those of specific embodiments 1 to 6.
[0053] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the treatment time in step 3 ② is 10s to 60s and the temperature of the alkaline passivating agent in step 3 ② is 25° C. to 50° C. The other steps are the same as those in specific embodiments 1 to 7.
[0054] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the drying temperature in step 4 is 40° C. to 60° C. The other steps are the same as those in specific embodiments 1 to 8.
[0055] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the natural aging time in step 5 is 10 to 30 days. The other steps are the same as those in specific embodiments 1 to 9.
[0056] The following examples are used to verify the beneficial effects of the present invention:
[0057] Example 1: A short-process method for preparing a strong hydrophobic passivation film on the surface of a titanium-zinc plate is specifically completed by the following steps:
[0058] 1. Pickling:
[0059] Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for 3 minutes to obtain a pickled titanium zinc plate;
[0060] The volume ratio of sulfuric acid to nitric acid in the pickling solution described in step 1 is 1:1;
[0061] The total concentration of sulfuric acid and nitric acid in the pickling solution described in step 1 is 20 mL / L;
[0062] The mass fraction of sulfuric acid described in step 1 is 98%, and the mass fraction of nitric acid is 65%;
[0063] The composition of the titanium zinc plate described in step 1 is as follows by mass percentage: Cu: 0.2%, Ti: 0.13%, Al: 0.011%, and the balance is Zn;
[0064] The thickness of the titanium zinc plate described in step 1 is 1.0 mm;
[0065] The temperature of the pickling solution described in step 1 is 30°C;
[0066] 2. Washing:
[0067] The pickled titanium-zinc plate was placed in water and rinsed for 3 minutes to obtain a water-washed titanium-zinc plate;
[0068] 3. Passivation:
[0069] ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent;
[0070] The concentration of sodium hydroxide in the alkaline passivating agent described in step 3① is 40g / L, the concentration of sodium phosphate is 50g / L, the concentration of sodium carbonate is 15g / L, and the concentration of sodium silicate is 15g / L;
[0071] ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 40kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0072] The processing time described in step 3② is 20s;
[0073] The temperature of the alkaline passivating agent described in step 3② is 40°C;
[0074] 4. Drying:
[0075] The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate;
[0076] The drying temperature in step 4 is 50°C;
[0077] 5. Natural aging:
[0078] The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time, and after the natural aging is completed, a titanium-zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface is obtained;
[0079] The natural aging time described in step 5 is 30 days.
[0080] The actual picture of the titanium zinc plate with a silvery white passivation film having strong hydrophobicity and self-cleaning properties on the surface obtained in Example 1 is shown in Figure 3 The salt spray corrosion test data is shown in Table 1:
[0081] Table 1 Corrosion test data of the highly hydrophobic and self-cleaning silver-white passivation film in Example 1 in a 5wt.% neutral salt spray environment
[0082]
[0083] Example 2: A short-process method for preparing a strong hydrophobic passivation film on the surface of a titanium-zinc plate is specifically completed by the following steps:
[0084] 1. Pickling:
[0085] Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for 4 minutes to obtain a pickled titanium zinc plate;
[0086] The volume ratio of sulfuric acid to nitric acid in the pickling solution described in step 1 is 1:1;
[0087] The total concentration of sulfuric acid and nitric acid in the pickling solution described in step 1 is 30 mL / L;
[0088] The mass fraction of sulfuric acid described in step 1 is 98%, and the mass fraction of nitric acid is 65%;
[0089] The composition of the titanium zinc plate described in step 1 is as follows by mass percentage: Cu: 0.3%, Ti: 0.22%, Al: 0.012%, and the balance is Zn;
[0090] The thickness of the titanium zinc plate described in step 1 is 1.3 mm;
[0091] The temperature of the pickling solution described in step 1 is 30°C;
[0092] 2. Washing:
[0093] The pickled titanium-zinc plate was placed in water for 6 minutes to obtain a washed titanium-zinc plate;
[0094] 3. Passivation:
[0095] ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent;
[0096] The concentration of sodium hydroxide in the alkaline passivating agent described in step 3① is 50g / L, the concentration of sodium phosphate is 60g / L, the concentration of sodium carbonate is 20g / L, and the concentration of sodium silicate is 20g / L;
[0097] ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 75kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0098] The processing time described in step 3② is 25s;
[0099] The temperature of the alkaline passivating agent described in step 3② is 47°C;
[0100] 4. Drying:
[0101] The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate;
[0102] The drying temperature in step 4 is 55°C;
[0103] 5. Natural aging:
[0104] The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time, and after the natural aging is completed, a titanium-zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface is obtained;
[0105] The natural aging time described in step 5 is 28 days.
[0106] The actual picture of the titanium zinc plate with a silvery white passivation film having strong hydrophobicity and self-cleaning properties on the surface obtained in Example 2 is shown in Figure 4 The salt spray corrosion test data is shown in Table 2:
[0107] Table 2 Corrosion test data of the highly hydrophobic and self-cleaning silver-white passivation film in Example 2 under 5wt.% neutral salt spray environment
[0108]
[0109] Example 3: A short-process method for preparing a strong hydrophobic passivation film on the surface of a titanium-zinc plate, which is specifically completed by the following steps:
[0110] 1. Pickling:
[0111] Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for 5 minutes to obtain a pickled titanium zinc plate;
[0112] The volume ratio of sulfuric acid to nitric acid in the pickling solution described in step 1 is 1:1;
[0113] The total concentration of sulfuric acid and nitric acid in the pickling solution described in step 1 is 35 mL / L;
[0114] The mass fraction of sulfuric acid described in step 1 is 98%, and the mass fraction of nitric acid is 65%;
[0115] The composition of the titanium zinc plate described in step 1 is as follows by mass percentage: Cu: 0.4%, Ti: 0.35%, Al: 0.013%, and the balance is Zn;
[0116] The thickness of the titanium zinc plate described in step 1 is 1.8 mm;
[0117] The temperature of the pickling solution described in step 1 is 35°C;
[0118] 2. Washing:
[0119] The pickled titanium-zinc plate was placed in water and rinsed for 7 minutes to obtain a water-washed titanium-zinc plate;
[0120] 3. Passivation:
[0121] ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent;
[0122] The concentration of sodium hydroxide in the alkaline passivating agent described in step 3① is 60g / L, the concentration of sodium phosphate is 70g / L, the concentration of sodium carbonate is 22g / L, and the concentration of sodium silicate is 22g / L;
[0123] ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 80kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0124] The processing time described in step 3② is 30s;
[0125] The temperature of the alkaline passivating agent described in step 3② is 45°C;
[0126] 4. Drying:
[0127] The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate;
[0128] The drying temperature in step 4 is 47°C;
[0129] 5. Natural aging:
[0130] The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time, and after the natural aging is completed, a titanium-zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface is obtained;
[0131] The natural aging time described in step 5 is 26 days.
[0132] The actual picture of the titanium zinc plate with a silvery white passivation film having strong hydrophobicity and self-cleaning properties on the surface obtained in Example 3 is shown in Figure 5The salt spray corrosion test data are shown in Table 3:
[0133] Table 3 Corrosion test data of the highly hydrophobic and self-cleaning silver-white passivation film in Example 3 under 5wt.% neutral salt spray environment
[0134]
[0135]
[0136] Example 4: A short-process method for preparing a strong hydrophobic passivation film on the surface of a titanium-zinc plate is specifically completed by the following steps:
[0137] 1. Pickling:
[0138] Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for 8 minutes to obtain a pickled titanium zinc plate;
[0139] The volume ratio of sulfuric acid to nitric acid in the pickling solution described in step 1 is 1:1;
[0140] The total concentration of sulfuric acid and nitric acid in the pickling solution described in step 1 is 40 mL / L;
[0141] The mass fraction of sulfuric acid described in step 1 is 98%, and the mass fraction of nitric acid is 65%;
[0142] The composition of the titanium zinc plate described in step 1 is as follows by mass percentage: Cu: 0.5%, Ti: 0.42%, Al: 0.015%, and the balance is Zn;
[0143] The thickness of the titanium zinc plate described in step 1 is 2.2 mm;
[0144] The temperature of the pickling solution described in step 1 is 35°C;
[0145] 2. Washing:
[0146] The pickled titanium-zinc plate was placed in water for 9 minutes to obtain a water-washed titanium-zinc plate;
[0147] 3. Passivation:
[0148] ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent;
[0149] The concentration of sodium hydroxide in the alkaline passivating agent described in step 3① is 65g / L, the concentration of sodium phosphate is 75g / L, the concentration of sodium carbonate is 25g / L, and the concentration of sodium silicate is 25g / L;
[0150] ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 90kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0151] The processing time described in step 3② is 45s;
[0152] The temperature of the alkaline passivating agent described in step 3② is 50°C;
[0153] 4. Drying:
[0154] The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate;
[0155] The drying temperature in step 4 is 50°C;
[0156] 5. Natural aging:
[0157] The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time, and after the natural aging is completed, a titanium-zinc plate having a silver-white passivation film with strong hydrophobicity and self-cleaning properties on the surface is obtained;
[0158] The natural aging time described in step 5 is 30 days.
[0159] The actual picture of the titanium zinc plate with a silvery white passivation film having strong hydrophobicity and self-cleaning properties on the surface obtained in Example 4 is shown in Figure 6 The salt spray corrosion test data are shown in Table 4:
[0160] Table 4 Corrosion test data of the highly hydrophobic and self-cleaning silver-white passivation film in Example 4 in a 5wt.% neutral salt spray environment
[0161]
[0162] Comparative Example 1: The difference between this embodiment and embodiment 1 is that in step 3①, chromium trioxide, citric acid and zinc chloride are dissolved in water to obtain a passivating agent; the concentration of chromium trioxide in the passivating agent described in step 3① is 10 g / L, the concentration of citric acid is 10 g / L, and the concentration of zinc chloride is 10 g / L. Other steps and parameters are the same as those in embodiment 1.
[0163] The actual picture of the titanium zinc plate with the surface passivation film obtained in Comparative Example 1 is shown in Figure 7 The salt spray corrosion test data are shown in Table 5:
[0164] Table 5 Corrosion test data of the surface passivation film obtained in comparative example 1 in a 5wt.% neutral salt spray environment
[0165]
[0166] Comparative Example 2: The difference between this embodiment and embodiment 1 is as follows: Step 3②, immersing the washed titanium zinc plate in an alkaline passivating agent, and simultaneously adopting ultrasonic treatment, with the working frequency controlled at 40kHz, and after a period of treatment, taking out the titanium zinc plate to obtain a passivated titanium zinc plate;
[0167] The processing time described in step 3② is 120s;
[0168] The temperature of the passivating agent in step 3② is 50° C. The other steps and parameters are the same as those in Example 1.
[0169] The actual picture of the titanium zinc plate with the surface passivation film obtained in Comparative Example 2 is shown in Figure 8 The salt spray corrosion test data are shown in Table 6:
[0170] Table 6 Corrosion test data of the surface passivation film obtained in comparative example 1 in a 5wt.% neutral salt spray environment
[0171]
Claims
1. A short-process preparation method for a strong hydrophobic passivation film on the surface of a titanium-zinc plate, characterized in that The preparation method is specifically completed according to the following steps:
1. Pickling: Mix sulfuric acid, nitric acid and water to obtain a pickling solution; immerse the titanium zinc plate in the pickling solution for pickling for a period of time to obtain a pickled titanium zinc plate; 2. Washing: The pickled titanium-zinc plate is placed in water for rinsing to obtain a water-washed titanium-zinc plate; 3. Passivation: ①, dissolve sodium hydroxide, sodium phosphate, sodium carbonate and sodium silicate in water to obtain an alkaline passivating agent; ②, immerse the washed titanium zinc plate in an alkaline passivating agent, and use acoustic-fluid coupled cavitation treatment at the same time, with the working frequency controlled at 10kHz to 100kHz. After a period of treatment, take out the titanium zinc plate to obtain a passivated titanium zinc plate; 4. Drying: The passivated titanium-zinc plate is placed in a drying machine for drying to obtain a dry passivated titanium-zinc plate; 5. Natural aging: The dried passivated titanium-zinc plate is hung in a dry environment for natural aging for a period of time. After the natural aging, a titanium-zinc plate with a silver-white passivation film having strong hydrophobicity and self-cleaning properties on the surface is obtained.
2. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The volume ratio of sulfuric acid to nitric acid in the pickling solution described in step 1 is 1:1; the total concentration of sulfuric acid and nitric acid in the pickling solution described in step 1 is 15 mL / L to 45 mL / L.
3. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The mass fraction of sulfuric acid described in step 1 is 95% to 98%, and the mass fraction of nitric acid is 63% to 68%.
4. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The composition of the titanium zinc plate described in step 1 is as follows by mass percentage: Cu: 0.08% to 1.0%, Ti: 0.07% to 0.5%, Al≤0.015%, and the remainder is Zn; the thickness of the titanium zinc plate described in step 1 is 0.3mm to 3mm.
5. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The temperature of the pickling solution in step 1 is 25°C to 50°C; the pickling time in step 1 is 1 min to 10 min.
6. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The flushing time described in step 2 is 1 min to 10 min.
7. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The concentration of sodium hydroxide in the alkaline passivating agent described in step 3① is 20g / L~80g / L, the concentration of sodium phosphate is 20g / L~80g / L, the concentration of sodium carbonate is 5g / L~25g / L, and the concentration of sodium silicate is 5g / L~25g / L.
8. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The treatment time described in step 3 ② is 10s to 60s; the temperature of the alkaline passivating agent described in step 3 ② is 25°C to 50°C.
9. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The drying temperature in step 4 is 40°C to 60°C.
10. The method for preparing a short-process strong hydrophobic passivation film on the surface of a titanium-zinc plate according to claim 1, characterized in that The natural aging time described in step 5 is 10 to 30 days.